Maturity, oil source rock and retorting potential of perhydrous coals in the Central Tertiary Basin, Spitsbergen - Uguna, Jacob Onyebuolise (2016)
The occurrence of perhydrous (oil-prone) coal deposits within the Firkanten Formation of the Central Tertiary Basin (CTB) in Spitsbergen, is well documented and the oil present is reportedly sourced from the coals (Mokogwu, 2011; Marshall et al., 2015a). This study uses a total of 146 coal samples covering areas of the eastern coalfield (Bassen, Breinosa and Lunckefjellet) and the western coalfield (Colesdalen) of the CTB to investigate the maturity, oil source rock potential, and retorting potential of these perhydrous coals. In addition, the controls on the oil potential of the coals are considered to provide measures that could be used to determine the optimum resource areas in the basin. Samples were provided by Store Norske Spitsbergen Kulkompani AS, and include drill cores, mine sections and outcrop sections from the Svea, Longyear, Svarteper and Askeladden seams (eastern coalfield), and the Sputnik and Verkny seams (western coalfield).